2003
DOI: 10.1016/s1441-3582(03)70119-0
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Fundraising Efficiency by Segmenting Donors

Abstract: In recent years, private individual giving has gained much importance as a source of support for non-profit organisations (NPOs). Most academics consider psychographic criteria as the basis for segmenting and targeting donors. In marketing practice, however, fundraisers are often confined to socio-demographic data on their target groups. This article suggests certain socio-demographic characteristics, when combined with behavioural aspects, can be traced back to fundamental dimensions that represent efficient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
76
3
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(88 citation statements)
references
References 24 publications
6
76
3
3
Order By: Relevance
“…A key insight of our findings is that scientific data donation differs in some important ways from other charitable donations. Most prior studies on charitable donation have suggested that in general, people's propensity to donate increases with age and education, and that females donate more often than males (Schlegelmilch et al, 1997;Simmons and Emanuele, 2007;Srnka et al, 2003). However, our findings suggest that this is not the case for scientific data donation.…”
Section: Donating Contextual Data Is Not the Same As Other Types Of Dcontrasting
confidence: 86%
“…A key insight of our findings is that scientific data donation differs in some important ways from other charitable donations. Most prior studies on charitable donation have suggested that in general, people's propensity to donate increases with age and education, and that females donate more often than males (Schlegelmilch et al, 1997;Simmons and Emanuele, 2007;Srnka et al, 2003). However, our findings suggest that this is not the case for scientific data donation.…”
Section: Donating Contextual Data Is Not the Same As Other Types Of Dcontrasting
confidence: 86%
“…Greene & Baron, 2001). An average donor supporting primarily ingroup-organizations is likely to put a greater value on personal experiences (higher chance of personally knowing someone who can benefit from the donation, Small & Simonsohn, 2008;Srnka et al, 2003) or on group-specific responsibilities (believing that you have a responsibility to help members of your own group but not a responsibility to help those outside of your group, Erlandsson, Björklund & Bäckström, 2015;Baron, Ritov & Greene, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…To be able to take differences in what causes people prefer into consideration, it is necessary to give participants the opportunity to select among causes and to disentangle the act of selecting a cause from the overall incidence and amount of donations. In addition, most of the participants in these studies were in their 20s, although medical causes may have greater moral urgency among older persons (Neumayr & Handy, 2019;Srnka, Grohs, & Eckler, 2003).…”
Section: Moral Foundations Theory and Charitable Givingmentioning
confidence: 99%